2009
DOI: 10.1007/s00464-009-0326-5
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery for the treatment of rectal cancer: comparison of wound complication rates with and without neoadjuvant radiation therapy

Abstract: Not unexpectedly, the wound complication rate was higher in the XRT group. However, 82% of those wounds were minor, and 91% were treated without any additional surgery or intervention. Although a significant concern, wound complications do not prohibit TEM treatment after neoadjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 23 publications
0
49
2
4
Order By: Relevance
“…Marks et al [155] retrospectively reviewed the short-term outcomes in 43 rectal cancer patients treated with TEM after neoadjuvant long-course CRT (CRT group) and in 19 patients treated with TEM alone. They found higher morbidity rates in the CRT group than in the TEM group (33% vs. 5.3%, p<0.05).…”
Section: Expc: 909%]mentioning
confidence: 99%
“…Marks et al [155] retrospectively reviewed the short-term outcomes in 43 rectal cancer patients treated with TEM after neoadjuvant long-course CRT (CRT group) and in 19 patients treated with TEM alone. They found higher morbidity rates in the CRT group than in the TEM group (33% vs. 5.3%, p<0.05).…”
Section: Expc: 909%]mentioning
confidence: 99%
“…Local excision of advanced rectal cancers with curative intent remains a debatable issue. The review recommended that TEM only be used for palliative cases in T2-T3 tumors, nevertheless, researchers in several studies have described that TEM is safe and effective for patients with rectal carcinoma pT2 N0 low risk after neoadjuvant therapy and pT3 N0 low risk and complete response after neoadjuvant therapy who refused abdominal surgery [4,5,[9][10][11][12][13]22,26,[30][31][32]. Our experience has shown that neoadjuvant therapy followed by TEM to treat T2-3 N0 rectal cancer is well tolerated and effective.…”
Section: Discussionmentioning
confidence: 90%
“…Albeit, in Europe and in USA the preoperative prophylactic antibiotic administration, together with the pre-and postoperative rectal lumen irrigation with povidone-iodine are treadmill, 3,7,8 they are not widely accepted as reported in the Chen's et al 1 . In fact, according to "Application of Antimicrobial Drugs Guide for Perioperative Prevention" published in Chinese Medical Association Surgery Branch in 2006, TEM procedure does not need for prophylactic administration of antibiotics.…”
Section: In Clinical Values Of Preoperative Use Of Antibiotics Inmentioning
confidence: 99%
“…3 In the Chen's et al article, patients who underwent to n-CRT are not reported, 1 even if, recently, it is possible to observe a fast increase of association of neoadjuvant therapy and transanal procedures (with TEM or other platforms). 3,7,8 The impact of the n-CRT on postoperative outcomes in these patients is still debated, anyway the use of this therapy should be considered during the evaluation of the antibiotics management strategy.…”
Section: In Clinical Values Of Preoperative Use Of Antibiotics Inmentioning
confidence: 99%